Utilizing Comics as a Learning Media to Improve Students’ Arabic Speaking Skills - Setiyadi, Alif Cahya; Anhar, Anhar; Muttaqin, Hasan (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study aims to identify the characteristics of comic-based teaching materials for Al-Muhadatsah instruction and to evaluate their effectiveness in enhancing Arabic speaking skills among participants in the language program at Pondok Modern Darussalam Gontor. The integration of visual elements, contextual vocabulary, and culturally relevant narratives provides an engaging and interactive learning experience that fosters students’ motivation and enthusiasm for Arabic conversation. This research adopts a Research and Development approach within an applied research framework. Data were collected through observation, interviews, tests, questionnaires, and documentation, and were analysed using the Wilcoxon Signed Ranks Test with the assistance of SPSS 29. The findings reveal two main results. First, the developed teaching materials consist of eight titles based on learners’ daily activities, supported by contextually appropriate illustrations and vibrant colours that enhance their appeal. Second, the quantitative analysis confirms the effectiveness of these materials, as indicated by a significance value of 0.002, which is lower than the 0.05 threshold. These results indicate that comic-based teaching materials significantly improve the Arabic speaking skills of the program participants. This study highlights the importance of innovative instructional resources and encourages educators to implement creative strategies to enhance student engagement. Future research is recommended to explore the development of Al-Muhadatsah materials in the form of cartoon videos to further support language acquisition.